Organização do trabalho dos treinadores de vôlei de praia de alto rendimento do circuito brasileiro de 2005 - Batista, Gilmário Ricarte (2006)
Beach Volleyball (BV) has reached constant prominence in the last decade in Brazil by means of the national communication, its international conquests and for its spreading as a recreational sport. Therefore, it is noticed that the Beach Volleyball Coaches (BVC) are considered to be the class of the highest importance for the performance and the evolution of the sport. So, from the significant importance that this work organization has in the national sporting environment, there comes the need to analyze its features. Hence, this study aims at analyzing the features of the organization of the work of the BVC of high revenue of the Brazilian Circuit 2005. This is a transversal descriptive research. There has been used as a researching instrument a questionnaire with open, closed and evaluation questions. The informants of this study consisted of BVC of high revenue of the Brazilian Circuit 2005 (N=30). The results have revealed that 50% of the BVC are from the Northeastern area, 47% from the Southeast and 3% from the South. The average of time of experience in the activity is 9,43 ± 7,04 years. As for the education level, it was observed that 50% of the BVC have a bachelor degree in physical education teachings and 23% only have high school levels. The main difficulties presented by the BVC were the professional instability, with 74%, and the remuneration, with 70%. The staff characterization of the BVC came with two factors which explain 78,6% of the total variance of the obtained answers. The former was labeled as a preventive group, being composed of two variables, namely: psychologist, nutritionist and physiotherapist; and the latter was labeled as a technical support group consisting of two variables, namely: auxiliary technician and physical coach. The characterization of the development of the Brazilian BVC came with two factors, accounting for 62,2% of the total variance of the obtained answers. The first factor was labeled as a technical development group and it has obtained the largest load with 0,859 in the professional formation of BVC. The second factor was labeled as an administrative structure group and it has obtained the largest load, with 0,831 in the calendar of national competitions of BV. It is thus concluded, through this study, that the intersection of the prevention group with the technical support and with the technical development groups, when consolidated by the administrative structure of BV, can generate great results in the organization of the work.